STRATEGI PENGEMBANGAN DESTINASI WISATA UNGGULAN MELALUI PENDEKATAN CONVERGENCE MODEL OF COMMUNICATION DI KABUPATEN ACEH JAYA - Iwan Doa Sempena Iwan; Saiful Amri; Desi Maulida; Safrida; Cut Herawati (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
Aceh Jaya Regency is striving to develop its tourism potential into a leading destination through the implementation of RIPPARDA which includes potential identification, infrastructure development, promotion, and community empowerment, but still faces challenges such as limited human resources, community apathy, negative views on the benefits of tourism, and top-down management. This study aims to determine the persuasive communication approach taken by the government to the community by creating an interactive relationship achieved through communication convergence. The study used a qualitative method with data collection techniques from interviews, observations, and documentation studies. The research informants consisted of the government at the Aceh Jaya Regency Tourism Office, Pokdarwis, the local community, business actors and tourists. This study used the Convergence Model of Communication approach. The results of the study indicate that the process of developing superior tourist destinations in Aceh Jaya Regency does not fully reflect the convergence of meaning between the government and the community. This is caused by the still limited dialogic interaction, reciprocal participation, and equality in the process of information exchange and decision-making. Thus, it is necessary to strengthen two-way communication that is participatory and collaborative in order to achieve mutual understanding and create synergy in realizing inclusive and sustainable tourism development.